Anti-collapse resistance mechanisms in corner-supported modular steel buildings. (July 2020) - Alembagheri, M.; Sharafi, P.; Hajirezaei, R.; Tao, Z.
Abstract: Due to different integration strategies and stability requirements, the robustness analysis of multi-story modular buildings, made of volumetric units, requires collapse capacity analysis of various scenarios, corresponding to the loss of supports and notional removal of a part of ground floor modules. In this paper the results of a parametric analysis on the progressive collapse response of typical corner supported modular steel buildings are presented. The focus is on the effects of inter-modular connections' design on the anti-collapse resistance of these buildings. To that end, the effects of inter-modular connections translational behaviour, rotational stiffness of inter-modular connections, their removal time, and the rigidity of modules on the buildings' response are studied. Various module loss scenarios are imposed to a six-story modular building and its dynamic progressive collapse responses are investigated through alternative load path method. The collapse modes and anti-collapse resistance capacity of the building are studied, and some design considerations are proposed accordingly. The results show the significant effect of the translational behaviour of the connections, especially in shear. The rotational stiffness is shown not to have considerable contribution to maintaining the overall stability, provided that the modules individually act as complete rigid moment frames. On the other hand, while increasing the removal time, to the level of vertical natural period of the building, can considerably reduce its dynamic collapse response, the modules' rigidity shows no significant effect on the gravity-induced collapse resistance of the modular buildings. Highlights: A parametric analysis of the progressive collapse response of corner supported modular steel buildings. The effects of inter-connections translational behaviour, rotational stiffness, removal time, and modules rigidity. Dynamic progressive collapse response analysis through alternative load path method. Study of collapse modes and anti-collapse resistance capacity of the building and proposing some design considerations.